RO membrane/polyamide layer synthesis - Zhang, Xin (2009)
Polyamide Reverse Osmosis membrane synthesis is the primary step for further research on polyamide Forward Osmosis membrane. This project, interfacial polarization of polyamide selective layer, is incorporated with the synthesis of polysulfone substrate layer.